2005
DOI: 10.1213/01.ane.0000180766.74782.7e
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Endothelin in Neuropathic Pain After Chronic Constriction Injury of the Sciatic Nerve

Abstract: The purpose of this study was to explore the role of endothelin in neuropathic pain. Endothelins (ET) are a family (ET-1, ET-2, ET-3) of ubiquitously expressed peptides involved in control of vascular tone. Injected ET-1 causes intense pain via activation of ETA receptors, modulated by analgesic signals initiated by ETB receptor activation. Using a rat model of chronic constriction injury of the sciatic nerve, we found that pharmacologic ETA receptor antagonism acutely and significantly reduced thermal and mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…1998a), injected subcutaneously into the plantar surface of the hind paw, (Baamonde et al 2004;Balonov et al 2006;Gokin et al 2001;Houck et al 2004;Menendez et al 2003b;Piovezan et al 1998Piovezan et al , 2004Verri et al 2004Verri et al , 2005 or skin of the back (Mujenda et al 2007), and injected into tumor-bearing tissues Schmidt et al 2007;Wacnik et al 2001). In contrast, the newer ET A receptor-selective antagonists have been administered systemically (Chichorro et al 2006a;Klass et al 2005;Matwyshyn et al 2006;Piovezan et al 2000;Trentin et al 2006). Because we were interested in the role of ET A receptors near the tumor, presumably on the terminals of C nociceptors, we chose BQ-123 as the ET A receptor-selective antagonist as it has been shown to be effective when injected into peripheral tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1998a), injected subcutaneously into the plantar surface of the hind paw, (Baamonde et al 2004;Balonov et al 2006;Gokin et al 2001;Houck et al 2004;Menendez et al 2003b;Piovezan et al 1998Piovezan et al , 2004Verri et al 2004Verri et al , 2005 or skin of the back (Mujenda et al 2007), and injected into tumor-bearing tissues Schmidt et al 2007;Wacnik et al 2001). In contrast, the newer ET A receptor-selective antagonists have been administered systemically (Chichorro et al 2006a;Klass et al 2005;Matwyshyn et al 2006;Piovezan et al 2000;Trentin et al 2006). Because we were interested in the role of ET A receptors near the tumor, presumably on the terminals of C nociceptors, we chose BQ-123 as the ET A receptor-selective antagonist as it has been shown to be effective when injected into peripheral tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, systemic administration of an ET A receptor-selective antagonist attenuated mechanical allodynia in the streptozotocin-induced diabetic rat model of neuropathic pain (Jarvis et al 2000) and heat and mechanical hyperalgesia produced by chronic constriction injury of the sciatic nerve (Klass et al 2005). However, a similar constriction injury to the infraorbital nerve produced mechanical allodynia that was attenuated by systemic administration of an ET B receptor-selective antagonist (Chichorro et al 2006a).…”
Section: Role Of Et-1 In Inflammatory Neuropathic and Tumor-evoked mentioning
confidence: 99%
“…In mice with neuropathic pain after chronic constriction injury of the sciatic nerve Klass et al [16] found that endothelin was a mediator of pain in general. They suggest that their results motivate studies of endothelin as a potential novel therapy for neuropathic pain.…”
Section: Immune Markers and Neuropeptidesmentioning
confidence: 99%
“…in a diabetic rat model of neuropathic pain [15,18]. Intravenous ET-B, but not ET-A, receptor antagonist reduces mechanical allodynia in rats with trigeminal neuropathic pain [3].…”
Section: Discussionmentioning
confidence: 99%
“…whereas local or systemic ET-receptor antagonists attenuate a variety of nociceptive states [1,3,7,11,15,[18][19][20]26]. However, little is known about the role of ET receptors found in the spinal cord in nociception [23].…”
Section: Introductionmentioning
confidence: 99%